Efektivitas Model STEAM Berbantuan Media Loose Parts untuk Meningkatkan Kemampuan Kognitif Anak Usia Dini - Tajqiyah, Lina; Dwijayanti, Ida; Nugroho, Aryo Andri; Marfuah, Siti; Surya, Adi Darma (AS-SABIQUN, 2024)
This research addresses the issue of the lack of ideal and enjoyable learning for early childhood, which can impact the underdeveloped and suboptimal cognitive abilities of children. The aim of this study is to analyze the effectiveness of using the STEAM model with the assistance of Loose Parts media in improving the cognitive abilities of early childhood. The research method employed is quasi-experimental, with the sampling technique involving all students from TK Pertiwi 08.03 Nalumsari classes B1 and B2. Data analysis involves descriptive analysis and an independent sample t-test. The results indicate that the STEAM model with the assistance of natural Loose Parts media has a positive impact on the cognitive abilities of early childhood. The experimental group, which received learning with this model, showed a significant improvement in cognitive abilities compared to the control group. The t-test statistic yielded a value of t = 15.555 > t-table = 2.030, indicating a significant difference between the two groups. Thus, it can be concluded that the STEAM model with the assistance of natural Loose Parts media is effective in improving the cognitive abilities of early childhood.